2010
DOI: 10.1002/cphc.201000115
|View full text |Cite
|
Sign up to set email alerts
|

Silver Coated Platinum Core–Shell Nanostructures on Etched Si Nanowires: Atomic Layer Deposition (ALD) Processing and Application in SERS

Abstract: A new method to prepare plasmonically active noble metal nanostructures on large surface area silicon nanowires (SiNWs) mediated by atomic layer deposition (ALD) technology has successfully been demonstrated for applications of surface-enhanced Raman spectroscopy (SERS)-based sensing. As host material for the plasmonically active nanostructures we use dense single-crystalline SiNWs with diameters of less than 100 nm as obtained by a wet chemical etching method based on silver nitrate and hydrofluoric acid solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The plasmonic surfaces, which include solid substrate with metallic nanostructures and chemically synthesized noble metal colloids, and their fabrication methods were reviewed in a number of papers [ 15 , 16 , 17 ]. From another side, a number of publications have shown that different porous materials can be used as a matrix for SERS-active metals, for example: alumina [ 18 ], porous Si/SiO 2 [ 19 ], porous silicon [ 20 ], silicon nanowires [ 9 , 21 , 22 ], porous titanium oxide [ 23 ] and porous silver [ 13 ]. As is well-known, the bio-friendly properties [ 24 ] of porous silicon have been proven to act as a biocompatible and biodegradable material [ 25 , 26 ], as shown in a number of papers related to its biomedical applications [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The plasmonic surfaces, which include solid substrate with metallic nanostructures and chemically synthesized noble metal colloids, and their fabrication methods were reviewed in a number of papers [ 15 , 16 , 17 ]. From another side, a number of publications have shown that different porous materials can be used as a matrix for SERS-active metals, for example: alumina [ 18 ], porous Si/SiO 2 [ 19 ], porous silicon [ 20 ], silicon nanowires [ 9 , 21 , 22 ], porous titanium oxide [ 23 ] and porous silver [ 13 ]. As is well-known, the bio-friendly properties [ 24 ] of porous silicon have been proven to act as a biocompatible and biodegradable material [ 25 , 26 ], as shown in a number of papers related to its biomedical applications [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Few examples of ALD of Ag coatings have also been reported previously. [20][21][22][23][24][25] In the cases where AA-CVD was used, nonenvironmentally friendly solvents, such as THF and toluene, were used in combination with organometallic precursors. 10,11,16 Concerning the design of Ag metalorganic precursors, previous works have introduced different systems, including β-diketonate adducts Ag(hfac))(L) 26 or Ag(fod)(L),…”
Section: Introductionmentioning
confidence: 99%
“…A critical parameter in delivering practical plasmonic devices is the material preparation methods, which should allow the production of nanostructures with tunable plasmonic properties. So far, nanomaterials and nanodevice manufacturing have traditionally followed two distinct routes: (a) the top-down approach, where a process starts from a uniform material and subsequently finer and finer tools are employed to create smaller structures, like lithographic processes [35][36][37] and/or ion beam nanofabrication [38] and (b) the bottom-up approach, where smaller components of atomic or molecular dimensions self-assemble together, according to a natural physical principle or an externally applied driving force, to give rise to larger and more organized systems, like atomic layer deposition [39], cold welding [40], flash thermal annealing [41,42], pattern transfer [43] and template stripping [44][45][46]. Practically, the top-down approach offers unequalled control and reproducibility down to a few nanometres in feature size but at high cost for large area manufacturing, while the bottom-up route applies for macroscopic scale nanopatterning albeit without the fine feature and reproducibility control.…”
Section: Introductionmentioning
confidence: 99%